1979
DOI: 10.1210/jcem-49-3-462
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis in Diabetes Mellitus*

Abstract: Experimentally diabetic rats have low serum 1,25-dihydroxyvitamin D, intestinal malabsorption of calcium, secondary hyperparathyroidism, and bone loss. To examine the hypothesis that abnormalities similar to those in the diabetic rat might explain human diabetic osteopenia, we studied calcium metabolism in 40 healthy control and 82 diabetic patients aged 18--75 yr [47 untreated: fasting plasma glucose (mean +/- SE), 267 +/- 8 mg/dl; 19 treated but hyperglycemic: glucose 305 +/- 24 mg/dl; 16 treated and in bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
4

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(47 citation statements)
references
References 32 publications
7
36
4
Order By: Relevance
“…Maternal and fetal corrected calcium val ues were significantly lower in diabetics than in controls, in agreement with the previous reports [15,19], On the other hand Heath et al [7] found no alterations in mineral values of nonpregnant diabetic subjects. We have not analyzed PTH.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Maternal and fetal corrected calcium val ues were significantly lower in diabetics than in controls, in agreement with the previous reports [15,19], On the other hand Heath et al [7] found no alterations in mineral values of nonpregnant diabetic subjects. We have not analyzed PTH.…”
Section: Resultssupporting
confidence: 92%
“…24,25(OH)2D values have been contra dictory in previous reports [1,6,7], The role of this metabolite is controversial [16]. The present and the previous study in nonpreg nant patients [1] showed low levels of the most active metabolite, l,25(OH)2D, in the group with type 1 diabetes.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…In most (17, 51, 59, 63, 67-72), but not all (69,73,74), case-control studies, patients with type 2 DM or glucose intolerance are found to have lower serum 25-OHD concentration compared with controls without diabetes (Table 3).…”
Section: Evidence From Observational Human Studies What Is the Associmentioning
confidence: 99%
“…Problems may be 2.67* *Significant difference in intragroup over follow-up time; **significant difference between the two study groups at the same follow-up time; ***significant difference between the two groups when compared overall Graph 3: Demographic details of the patients 1.74 *Significant difference between the study groups at baseline time of follow-up; **significant difference between the study groups at 1 year time of follow-up encountered by the clinician while planning dental implant surgeries in diabetic patients. 12 Hence, we assessed the clinicomicrobial and salivary profile of diabetic patients undergoing rehabilitation by dental implants. While evaluating the mean levels of IL-β during follow-up time, no significant correlation was obtained between the control group and diabetic group (p > 0.05) (Graph 1).…”
Section: Discussionmentioning
confidence: 99%